Indium-flush technique for C-band InAs/InP quantum dots - Jiajing Yuan; Calum Dear; Hui Jia; Jae-Seong Park; Yaonan Hou; Khalil El Hajraoui; Haotian Zeng; Huiwen Deng; Junjie Yang; Mingchu Tang; Siming Chen; Quentin M. Ramasse; et al. (APL Materials)
High-quality InAs/InP quantum dots (QDs) emitting at 1550 nm are indispensable to realize high-performance telecom C-band lasers. In general, a longer emission (>1550 nm) with a broad spectral character has been obtained with InAs/InP QDs. Here, we proposed the use of the indium-flush (IF) method to shorten the emission and improve the optical properties of InAs/InP QDs. By exploiting IF, the full-width at half-maximum of the room-temperature QD photoluminescence spectra is narrowed from 89.2 to 47.9 meV, with a blue shift of 300 nm (from 1824 to 1522 nm). The scanning transmission electron microscopy and electron energy loss spectroscopy results reveal the atomic-level mechanism of the IF method, which uniformly modify the height of InAs/InP QDs in a controlled manner and form distinct Al-rich and In-rich regions. Finally, InAs/InP (001) QD lasers with the IF method have been demonstrated with a low threshold current density per QD layer of 106 A/cm2. We demonstrated both in terms of mechanism model and device performance that the IF method could serve as a robust strategy for the growth of high-performance C-band InAs/InP QD lasers via molecular beam epitaxy.